Angular‐Encrypted Quad‐Fold Display of Nanoprinting and Meta‐Holography for Optical Information Storage. Issue 11 (3rd April 2022) - Wan, Shuai; Tang, Jiao; Wan, Chengwei; Li, Zhe; Li, Zhongyang
Abstract: The compactness and programmable versatility make metasurface a promising candidate for optical information encryption and storage. The typical strategy for storage capacity enhancement is essential to expand the metasurface multiplexing channels. Various controllable optical parameters are progressively realized for optical encryption and multiplexing, including wavelength, polarization, orbital angular momentum (OAM), forward/backward illumination, etc. However, as one of the most critical parameters, the incident wavevector ( k ) direction, namely, the illumination angle, has not been fully explored due to the lack of angular‐encoding capability. Herein, the angular‐encrypted freedom for both amplitude and phase manipulation is theoretically and experimentally achieved by strategically screening the architectural blocks to fulfill the complex‐amplitude requirement. Utilizing the angular‐induced alteration from surface plasmonic resonances (SPRs) and Fabry–Perot (FP) nanocavity resonances, a single angular‐encrypted metasurface has been successfully realized to simultaneously enable quad‐fold independent‐encoding channels, including dual‐holography and dual‐nanoprinting images. Compared to the spatial multiplexing scheme in many previous works, the angular‐encrypted strategy drastically boosts the information storage density and capacity. It is believed that the proposed angular‐encryption finds a new path to achieve multiplexing meta‐devices with fully controlled angular‐resolution and promisingly expands the information capacity for optical encryption with a brand‐new degree of freedom. Abstract : By strategically screening the architectural blocks to create angular‐encrypted freedom, a single metasurface is originally proposed to simultaneously exhibit quad‐fold angular‐encrypted displays, including dual‐holography and dual‐nanoprinting. These findings establish a new platform to achieve multiplexing meta‐devices with fully controlled angular‐resolution and promisingly expand the information capacity for optical encryption with a brand‐new degree of freedom.